Cryomorphological Topographies in the Study of Ice Caves - Manuel Gómez-Lende; Manuel Sánchez-Fernández (Geosciences, 2018)
The current interest in ice caves requires that their varied manifestations be known as accurately as possible in view of their responses to a global change and also to their great potential as paleoenvironmental witnesses. This phenomenon has been known about for a long time but is still scarcely studied from the point of view of its cryological values and the evolution and distribution of many of their morphologies. For this, the development of cryomorphological topographies from traditional techniques to geodetic surveys with different tools, including terrestrial laser scanning, is one of the most current ways to characterize and quantify this type of cryospheric phenomena. It represents a new kind of periglacial cartography whose use is feasible in spite of the difficulties these environments present.